Clinical outcomes of management of CVAD occlusions. Issue 9 (11th March 2011) - Peng, Calvin; Monagle, Paul; Newall, Fiona
Abstract : Central venous access device (CVAD) occlusions are commonly treated with tissue plasminogen activator (tPA). Eighty-seven patients with 97 catheters at The Royal Children's Hospital, Melbourne were given tPA as per clinical practice guidelines. Restoration of CVAD patency and long-term CVAD survival were measured. Cumulative CVAD restoration rates for tPA treatment were 68.5% and 78.7% after one and two doses, respectively. A significantly lower rate of successful tPA treatment was found in implantable ports (46.2% compared with 81% for Hickman catheters). CVAD time of survival until non-elective removal for 3 months, 6 months and 12 months was 64%, 57% and 47%, respectively. The authors conclude that tPA is safe and effective in extending the life of occluded CVADs occlusions by months to years but is less effective in implantable ports.